Kematian dalam Puisi “Jauh” Karya Joko Pinurbo: Kajian Semotika Riffaterre - Afrianto, M. Afdal; Nasution, Muhammad Ismail (Persona: Kajian Bahasa dan Sastra, 2024)
The aim of this research is to analyze the meaning of the poem "Jauh" in the poetry collection "Pants" by Joko Pinurbo in 1996 using a semiotic approach developed by Riffaterre. This approach was chosen because it can explore the meaning of the diction used by the poet. To describe the data, a qualitative descriptive method was applied. The data source was taken from the poem "Jauh" by Joko Pinurbo, while the supporting data was taken from various literature related to Riffaterre's semiotic theory and Indonesian poetry. The analysis process begins with heuristic reading to understand the denotative meaning, followed by hermeneutic reading to find the second (connotative) meaning. In conclusion, the poem "Far" describes someone who is thinking about his death. The symbols used in this poem refer to the concepts of death and rebirth, as well as the relationship between individuals and the world around them. This research will add to the treasures of developing literary studies which focus on poetry analysis using a semiotic approach